Placenta accreta spectrum disorders – detection rate and maternal outcomes following implementation of an institutional protocol. (17th February 2022) - Karkhanis, Pallavi; Ahmed, Irshad; Irani, Shirin
Abstract: Placenta accreta spectrum (PAS) disorders have been on the rise in recent years with increasing caesarean rates. The purpose of this prospective observational study was to describe our detection rates and to review outcomes in PAS after the introduction of an institutional screening and management protocol. Twenty-one patients with suspected PAS over 5 years were identified. 20/21 patients had an accurate determination of placental invasion and positive correlation with surgical and histopathological examination. Early morbidity (massive haemorrhage) was found in 7/21 patients, whilst late morbidity (hospital readmission) was found in 5/21 patients. There were no maternal deaths and admissions to intensive therapy unit (ITU). In summary, our centre demonstrated a high antenatal detection rate for PAS using an evidence-based protocol. This has led to timely intervention by an experienced multidisciplinary team and excellent outcomes. Immediate and delayed postoperative counselling was effective for optimal patient understanding and experience. Impact Statement: What is already known on this subject? With rising caesarean section rates, the incidence of placenta accreta spectrum (PAS) disorders is increasing. Despite this, most obstetricians have personally managed only a small number of patients with PAS. Moreover, there appears to be some debate over the optimal diagnostic and management strategy. What do the results of this study add? As the incidence increases, development of institutional screening and management protocol is a necessity for large units. Timely diagnosis, extensive pre and postoperative counselling and multidisciplinary teamwork ensure reduced early and late morbidity. What are the implications of these findings for clinical practice and/or further research? Evidence based screening protocols for PAS disorders reduce the likelihood of undiagnosed cases and should be developed in every unit. Consideration must also be given to standardisation of the diagnostic and management protocols, including contingency plan for emergencies.